Popular Culture. A Reply to Shusterman and Małecki - Snævarr, Stefán (The Nordic Journal of Aesthetics, 2009)
The article is a response to criticism of my two recent articles on Richard Shusterman’s view of popular culture by Shusterman and Małecki. The former maintains that I have misrepresented his view on Europe, the USA and popular culture. But I point out that he talks as if there is no popular culture in Europe due to Europe’s aristocratic traditions, and that the USA is a hotbed of popular culture thanks to its egalitarian traditions, and that Europe can be treated as a country comparable to the USA. He also says that I falsely think he is talking about popular culture while he is really talking about popular art. But I show that it is meaningless to talk about popular art without talking about popular culture and that as a pragmatist Shusterman should have understood that. I show that Małecki grossly misrepresents my article, maintaining that I am against all forms of popular art and against everything Shusterman says about popular art. I show that this is blatantly wrong.